2020
DOI: 10.1177/0954407020909241
|View full text |Cite
|
Sign up to set email alerts
|

A condensed dynamic model of a heavy-duty truck for optimization of the powertrain mounting system considering the chassis frame flexibility

Abstract: The existing powertrain mounting models of the heavy-duty truck for optimizing the mounts parameters cannot well describe the deformation of the chassis frame. To overcome this disadvantage, a new full vehicle model is proposed which embraces the view of system modeling and includes the frame flexibility. The model can achieve optimal parameters of the Powertrain Mounting System for isolating the vibration transmitted from the powertrain to the chassis. A model reduction technique, improved reduced system, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The derived dynamic equations are usually expressed in partial differential forms. The discretization modeling methods can be divided into three categories: the transfer matrix modeling method [32], the finite element modeling method [33][34][35][36], and one type of lumped mass modeling method [37][38][39]. Compared with the other two, the lumped mass modeling method could characterize the main features of complex rotating machines.…”
Section: Numerical and Experimental Analysis Of The Effect Of Eccentricmentioning
confidence: 99%
“…The derived dynamic equations are usually expressed in partial differential forms. The discretization modeling methods can be divided into three categories: the transfer matrix modeling method [32], the finite element modeling method [33][34][35][36], and one type of lumped mass modeling method [37][38][39]. Compared with the other two, the lumped mass modeling method could characterize the main features of complex rotating machines.…”
Section: Numerical and Experimental Analysis Of The Effect Of Eccentricmentioning
confidence: 99%
“…Particle swarm optimization is an evolutionary calculation method based on swarm intelligence. The system initializes a group of particles randomly through the system and searches for the optimal solution continuously and iteratively (Wang et al, 2018). The iteration formula is as follows:…”
Section: Improved Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…Many studies have shown that long-term exposure to low frequency and high-intensity vibration will seriously affect the physical and mental health of passengers. Therefore, research on vibration reduction of vehicle body and seat is of great significance to improve the driving comfort of vehicles and the physical and mental health of occupants [6][7][8].…”
Section: Introductionmentioning
confidence: 99%